Prevalence and prognostic role of lymphedema in patients with deep venous thrombosis and thrombophlebitis - Grigorean, Alexandru; Lindenblatt, Nicole; Luchsinger, Isabelle; Hobohm, Lukas; Konstantinides, Stavros V.; Münzel, Thomas; Barco, Stefano; Keller, Karsten (Lymphatic research and biology, 2024)
Background: Deep venous thrombosis (DVT) poses a substantial disease burden. Lymphedema may present with similar symptoms making the diagnosis process more difficult. Data on the epidemiology of lymphedema are lacking. - Methods: The German nationwide inpatient sample served to analyze all patients hospitalized owing to DVT and/or thrombophlebitis (referred to as DVT) of the legs in Germany between 2005 and 2020. We stratified these patients for additional lymphedema and analyzed the impact of lymphedema on adverse in-hospital events. - Results: Overall, 1,136,574 hospitalizations related to DVT were recorded in Germany during 2005-2020 (53.3% women; 51.3% aged ≥70 years). Lymphedema was coded in 9974 (0.9%) patient-cases (82.0% not elsewhere classified, 17.7% secondary lymphedema). Annual numbers of hospitalizations with lymphedema among DVT patients increased from 450 (2005) to 613 (2016) (β 0.57; 95% confidence interval [CI]: 0.48-0.66], p < 0.001) and decreased thereafter. Despite similar age, DVT patients with lymphedema had higher prevalence of cardiovascular diseases, chronic organ failure, and all types of investigated cancer. Prevalence of pulmonary embolism (PE) with shock/CPR (4.1% vs. 1.5%), acute renal failure (6.7% vs. 2.5%), and stroke (5.2% vs. 4.2%) was higher in DVT patients with lymphedema than without. Lymphedema was independently associated with PE with shock/CPR (OR: 2.1; 95% CI: 1.9-2.3) as well as death (OR: 1.3; 95% CI: 1.2-1.4). - Conclusions: Comorbidity conditions like cancer, obesity, and cardiovascular risk factors, and also infectious complications, were more prevalent in DVT patients with lymphedema than in those without. Lymphedema was independently associated with severe in-hospital complications, particularly when its genesis was related to severe comorbidities.
Online veröffentlicht: 21. Februar 2024
Gesehen am 06.05.2024